The Role of Human Resource Competence and Internal Control on Financial Reporting Quality - Tamang, Nurul Azizah; Haliah, Haliah (Transpublika Publisher, 2025)
This study addresses the issue of weak accountability and transparency in public sector financial management, which is often linked to limited human resource competence and ineffective internal control systems. The primary objective is to analyze how these two factors contribute to improving public sector financial governance. A systematic literature review method was used, reviewing scientific articles published between 2018 and 2025 obtained from Google Scholar, Semantic Scholar, and Crossref. The findings indicate that human resource competence including technical expertise, regulatory understanding, and integrity has a significant impact on budget accountability. Moreover, comprehensive internal control mechanisms, such as layered supervision, effective reporting systems, and periodic audits, play a critical role in reducing the risk of fraud and enhancing public trust. These results suggest that improving the capacity of public sector personnel and reinforcing internal controls are essential strategies for sustainable financial governance. The study implies that policymakers and institutions should invest in continuous training and strengthen audit frameworks to support effective financial management in the public sector.